Principles and problems in physical chemistry for biochemists - Price, Nicholas C. (Oxford University Press, 2001)
The book starts by introducing the laws of thermodynamics, and then uses these laws to derive the equations relevant to the student in dealing with chemical equilibria (including the binding of small molecules to proteins), properties of solutions, acids and bases, and oxidation-reduction processes. The student is thus shown how a knowledge of thermodynamic qualities makes it possible to predict whether, and how, a reaction will proceed